The Science of spice : understand flavor connections and revolutionize your cooking - Farrimond, Stuart (London, United Kingdom : Penguin Random House ; Dorling Kindersley, 2018)
Break new ground with this spice book like no other, from TV personality, food scientist and bestselling author, Dr Stuart Farrimond. Taking the periodic table of spices as a starting point, explore the science behind the art of making incredible spice blends and how the flavour compounds within spices work together to create exciting layers of flavour and new sensations. This is the perfect cookbook for curious cooks and adventurous foodies. Spice profiles - organised by their dominant flavour compound - showcase the world's top spices, with recipe ideas, information on how to buy, use, and store, and more in-depth science to help you release the flavours and make your own spice connections. There is also a selection of recipes using innovative spice blends, based on the new spice science, designed to brighten your palate and inspire your own culinary adventures. If you've ever wondered what to do with that unloved jar of sumac, why some spices taste stronger than others, or how to make your own personal garam masala, this inspirational guide has all the answers. Explore the world's best spices, be inspired to make your own new spice blends, and take your cooking to new heights. You'll turn to this beautiful and unique book time and again - to explore and to innovate.
Spice science -- What is a spice? -- Spices and their flavour compounds -- Periodic table of spices -- Creating spice pairings and blends -- World of spice -- Middle East -- Africa -- South Asia -- Southeast Asia -- East Asia -- The Americas -- Europe -- Spice Profiles -- Sweet Warming Phenols -- Warming Terpenes -- Fragrant Terpenes -- Earthy Terpenes -- Penetrating Terpenes -- Citrus Terpenes -- Sweet-Sour Acids -- Fruity Aldehydes -- Toasty Pyrazines -- Sulphurous Compounds -- Pungent Compounds -- Unique Compounds -- Recipes.
Includes index.
Keywords: COOKING (SPICES)